2009
DOI: 10.1007/s00294-009-0242-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes that are preferentially expressed in conidiogenous cell development of Metarhizium anisopliae by suppression subtractive hybridization

Abstract: The insect pathogenic fungus Metarhizium anisopliae is widely used as an insect biocontrol agent. The M. anisopliae conidium plays an important role in pathogenesis and disease transmission. The aim of this study was to identify genes whose expression is up-regulated during conidiogenous cell development. This is a powerful strategy for obtaining insight into the molecular events that regulate conidiation. We isolated genes that are preferentially expressed in the developing conidiophores of the common fungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…A standard curve was made to optimize the amplification efficiency with the primer pairs L1 (5'-GCACAAGAAGATACCGATGGC-3') and L2 (5'-CGATCCACTGGGTTCTCATTTA-3'). Gdpdh encoding gly ceraldehyde-3-phosphate dehydrogenase was selected as an internal control, and the primers of 5'-AGATGGAGGAGTTGGTGTTG-3' and 5'-GACTGCCCGCATTGAGAAG-3' were used for it [47]. The cycling conditions were 95°C for 3 min followed by 45 cycles of 95°C for 10 sec, annealing at 59°C ( Ntl ) or 60°C ( Gdpdh ) for 10 sec.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard curve was made to optimize the amplification efficiency with the primer pairs L1 (5'-GCACAAGAAGATACCGATGGC-3') and L2 (5'-CGATCCACTGGGTTCTCATTTA-3'). Gdpdh encoding gly ceraldehyde-3-phosphate dehydrogenase was selected as an internal control, and the primers of 5'-AGATGGAGGAGTTGGTGTTG-3' and 5'-GACTGCCCGCATTGAGAAG-3' were used for it [47]. The cycling conditions were 95°C for 3 min followed by 45 cycles of 95°C for 10 sec, annealing at 59°C ( Ntl ) or 60°C ( Gdpdh ) for 10 sec.…”
Section: Methodsmentioning
confidence: 99%
“…Data were square root arcsine transformed before being subjected to analysis of variance (ANOVA) for a completely randomized design. The means were separated using Tukey's multiple range test, carried out using DPS software [47]. Statistical significance was established at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…341 Data from subtractive cDNA libraries of M. anisopliae identified genes differentially expressed during growth on hemolymph, 342 during microcycle conidiation, 343 and in conidiogenous cells. 344 Although the number of unigenes reported in these studies is small, some ESTs were identified that putatively encode secondary metabolite biosynthetic enzymes. [341][342][343][344][345] 3.5.2 Transcriptome studies with Beauveria bassiana.…”
Section: Genome Survey Of Terpene Cyclasesmentioning
confidence: 99%
“…344 Although the number of unigenes reported in these studies is small, some ESTs were identified that putatively encode secondary metabolite biosynthetic enzymes. [341][342][343][344][345] 3.5.2 Transcriptome studies with Beauveria bassiana. EST sequencing of aerial conidia, submerged conidia and in vitro blastospores of B. bassiana revealed a highly plastic transcriptome with major differences among the different libraries.…”
Section: Genome Survey Of Terpene Cyclasesmentioning
confidence: 99%
“…The mature conidia from 1/4 SDAY plates were washed with 1% PBS and harvested to detect the expression levels of MaSom1 in WT, OE-4, OE-34, OE-55 and VT by qRT-PCR with the primer pair of MaSom1-QF/MaSom1-QR (Table S1). Total RNA extraction, cDNA reverse transcription, and qRT-PCR were performed according to the existing method [55]. The glyceraldehyde 3-phosphate dehydrogenase gene gpdh (GenBank accession No.…”
Section: Validation Of Masom1 Overexpression Strainsmentioning
confidence: 99%